Comprehensive Study on the Effectiveness of Material Management in the UK Construction Industry - Pulimood, Sharath Mathai (2008)
Material management has emerged as a significant management practice, which includes both the technical and economical efficiency that are necessary for an improved functioning of the construction industry. Scarcity of resources and an increase in competition has highlighted the necessity for sustainable material management. In this dissertation the author has conducted a comprehensive study on the effectiveness of material management in the UK construction industry. A detailed understanding of material management is essential as it constitutes 40- 60% of the total project cost, which in turn affects the success of a construction project. The current management techniques have been critically analyzed to further ascertain the benefits and limitations of material management from a practical perspective rather than a customary theoretical perspective. The study is based on personnel interviews, questionnaires and detailed research done through a wide range of related books, journals and online media releases to evaluate the effectiveness of material management which will allow one to see the material management concept and its strategies and techniques. This will include qualitative and quantitative data. The selective sample to be used will be selected from the management team, and from those on site. This should provide an understanding of material management and how different levels of management view the success of their strategies. As most of the objectives are measuring strategies and looking at effectiveness, a large proportion of the research will be conducted in the form of questionnaires. The results obtained will be gathered from various construction companies in UK. The quality of the feedback has a substantial impact on the results obtained from the questionnaires. The research findings suggest that material management is effective but there is still a lot of scope for improvement. Some of the areas to focus on are concerned with cost and time issues, providing more training to the staff, using more modern techniques that are available. If the above problems are mitigated then material management in the UK could be the way forward.